Antibacterial Potential of Agarwood Leaf Extract (Aguilaria Microcarpa Baill) Against Salmonella Typhi - Andi Indrawati; Suherman Baharuddin; Dewi Isnaeni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Aguilaria microcarpa Baill, commonly known as the Agarwood plant, is commonly used as a medicinal plant that is thought to be able to treat certain diseases because it contains chemical compounds in the form of alkaloids, flavonoids, glycosides, and tannins which can act as antioxidants and antibacterials and can be used as raw materials for the medicinal industry natural herbs. Testing in this research nature is semi-quantitative and is laboratory research in testing Aguilaria microcarpa Baill leaf extract based on characterization tests, chemical content tests, and antibacterial potential tests on growth activity of Salmonella typhi with inhibition zone parameters produced by the agar diffusion method. The results showed that Agarwood leaf extract (Aguilaria microcarpa Baill) with concentrations of 3%, 6%, 9%, and 12% w/v had the potential as an antibacterial against growth activity Salmonella thypi. The higher the concentration of the extract tested, the greater the inhibitory activity against bacterial growth. The most effective concentration is at a concentration of 12% w/v with a Sig value. 0.000 < 0.05 (Oneway Anova α = 0.05) in strong category inhibition ( 10 – 20 mm)